Criminology: explaining crime and its context - Brown, Stephen E. (Routledge, 2019)
Foundations for criminology -- Crime and criminology -- The relativity of law and crime -- Crime statistics and the distribution of crime -- Theories of crime -- Deterrence and rational choice theories of crime -- Individual theories of crime : a biosocial perspective -- Social structure theories of crime -- Social process theories of crime -- Social reaction theories of crime -- New directions : integration and a life-course perspective -- Types of crime -- Violent crime 11. economic crime -- Crimes without victims and victims without crimes -- Youth violence